PENGARUH ONLINE CUSTOMER REVIEW DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN MAKANAN PADA MARKETPLACE SHOPEEFOOD (Studi pada konsumen ShopeeFood di Jakarta) - Azaria, Phamendyta; Sagala, Jayanti (JOURNAL OF BUSINESS STUDIES, 2022)
This study aims to examine the effect of Online Customer Reviews and Discounts on Food Purchasing Decisions at the ShopeeFood marketplace. This research was carried out online by distributing questionnaires to respondents who live in Jakarta. The sampling technique uses purposive sampling. The data analysis method used is multiple linear regression. The results of the study show that (1) Online Customer Reviews have a positive and significant effect on Food Purchasing Decisions for ShopeeFood consumers in Jakarta (2) Discounts have a positive and significant effect on Food Purchase Decisions for ShopeeFood consumers in Jakarta (3) Online Customer Reviews and Discounts have a positive and significant effect significant impact on food purchasing decisions for ShopeeFood consumers in Jakarta.